2017
DOI: 10.1016/j.neuroimage.2016.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Predicting symptom severity in autism spectrum disorder based on cortical thickness measures in agglomerative data

Abstract: Machine learning approaches have been widely used for the identification of neuropathology from neuroimaging data. However, these approaches require large samples and suffer from the challenges associated with multi-site, multiprotocol data. We propose a novel approach to address these challenges, and demonstrate its usefulness with the Autism Brain Imaging Data Exchange (ABIDE) database. We predict symptom severity based on cortical thickness measurements from 156 individuals with autism spectrum disorder (AS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 97 publications
4
39
0
Order By: Relevance
“…7. They appear in the lingual, supra-marginal, post-and precentral areas, which are consistent with previous reports on Autism studying the group differences in developmental patterns of cortical thickness (Smith et al 2016;Scheel et al 2011), as well as found to be important in other prediction tasks (Moradi et al 2017).…”
Section: Most Discriminative Regionssupporting
confidence: 92%
“…7. They appear in the lingual, supra-marginal, post-and precentral areas, which are consistent with previous reports on Autism studying the group differences in developmental patterns of cortical thickness (Smith et al 2016;Scheel et al 2011), as well as found to be important in other prediction tasks (Moradi et al 2017).…”
Section: Most Discriminative Regionssupporting
confidence: 92%
“…It was also unclear from the reviewed studies in Supplementary Table 2 as to the developmental trajectory of ASD, with four studies reporting accelerated thinning (Auzias et al, 2016;Koolschijn and Geurts, 2016;Wallace et al, 2015;Zielinski et al, 2014) and another four studies reporting slowed thinning (Doyle-Thomas et al, 2013a;Khundrakpam et al, 2017;Sussman et al, 2015;Yang et al, 2016), reflecting the inconsistencies in ASD development observed for the whole brain volume (ICV). Despite this, increased CT was associated with poorer outcomes across multiple ASD severity measures, including social communication language ability Sharda et al, 2016aSharda et al, , 2016b and the ADOS (Moradi et al, 2017;Sato et al, 2013), supporting this measure as a useful biomarker of autism. Furthermore, several studies investigate the covariance of CT across all regions of the cortex, and have established altered correlations and reduced covariance in CT with Euclidean distance when comparing ASD with TDC (Bethlehem et al, 2017;Sato et al, 2013), which may reflect the long-distance under-connectivity indicative of autism (Kikuchi et al, 2015).…”
Section: Cortical Shapementioning
confidence: 93%
“…Many studies found correlations between brain structure and clinical severity of autism, such as the ADOS (Dougherty et al, 2016b;Grecucci et al, 2016;Khundrakpam et al, 2017;Moradi et al, 2017;Sato et al, 2013) and ADI-R (Floris et al, 2016;Xiao et al, 2017), which are considered the two 'gold standard' diagnostic evaluations for children with autism (Reaven et al, 2008), as well as the Clinical Evaluation of Language Fundamentals (CELF) (Sharda et al, 2016a), Intelligence Quotient (IQ) (Fredo et al, 2014;Sharda et al, 2016b), the Movement Assessment Battery for Children (MABC) (Hanaie et al, 2016), and the Repetitive Behaviour Scale-Revised (RBS-R) (Eisenberg et al, 2015). Of the studies outlined in Supplementary Table 8, several reported strong correlations (Pearson's r between 0.4 -0.5) with outcome (Eisenberg et al, 2015;Gebauer et al, 2015;Grecucci et al, 2016;Hanaie et al, 2016;Joseph et al, 2014;Knaus et al, 2017;Laidi et al, 2017;Mahajan et al, 2016).…”
Section: Classification Of Asd Diagnosis and Prediction Of Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging data has also been examined using machine learning approaches. Moradi et al (2017) predicted symptom severity of individuals with ASD based on cortical thickness using support vector regression (SVR) and ENet penalized linear regression. Participants included 156 individuals with ASD ages 8 to 40 years old.…”
Section: Support Vector Machinesmentioning
confidence: 99%